Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa di Sekolah Dasar - Mulyadi Mulyadi (Journal on Education, 2023)
One of the reasons for the low learning outcomes of students in Islamic Religious Education (PAI) is that the learning model used by the teacher is not appropriate, the teacher implements conventional one-way learning, only transferring information from the teacher to the students. The purpose of this research is to improve Islamic education learning outcomes through the application of discovery learning models. This research is a Classroom Action Research (PTK) which is carried out in 2 cycles consisting of planning, implementation, observation and reflection. As the subject of this research are students of SD Miftahul Iman Pekanbaru. The subject of this research was the second grade students of SDIT Iftahul Iman, which consisted of 24 students. Data collection techniques use observation and giving assignments in the core activities, in order to get information about the activeness of children in participating in the teaching and learning process. The results of this study stated that the learning outcomes of class II students at SDIT Miftahul Iman Pekanabaru Islamic Education increased as expected. This success was caused by the application of the discovery learning learning model, this was evident from the student learning outcomes which continued to increase from the first cycle to 66.66% student learning outcomes which achieved completeness while in the second cycle 87.5%.